The septal pore cap is an organelle that functions in vegetative growth and mushroom formation of the wood‐rot fungus Schizophyllum commune - Arend F. Van Peer; Fengfeng Wang; Kenneth G. A. Van Driel; Jan F. De Jong; Elly G. Van Donselaar; Wally H. Müller; Teun Boekhout; Luis G. Lugones; Han A. B. Wösten (Environmental Microbiology, 2010)
Summary Mushroom‐forming basidiomycetes colonize large areas in nature. Their hyphae are compartmentalized by perforated septa, which are usually covered by a septal pore cap (SPC). Here, we describe, for the first time, the composition and function of SPCs using the model system Schizophyllum commune . The SPC of S. commune was shown to consist of a proteinaceous matrix covered by a lipid membrane. The matrix was demonstrated to define the ultrastructure of the SPC and to consist of two main proteins, Spc14 and Spc33. Gene spc14 encodes a protein of 86 amino acids, which lacks known domain, signal or localization sequences. Gene spc33 encodes a 239 and a 340 amino acid variant. Both forms contain a predicted signal anchor that targets them to the ER. Immuno‐localization showed the presence of Spc33 in the SPC but not in ER. From this and previous reports it is concluded that the SPC is derived from this organelle. Inactivation of spc33 resulted in loss of SPCs and the inability to close septa. The latter may well explain why vegetative growth and mushroom formation were severely reduced in strains in which spc33 was inactivated.

Trehalose degradation and glucose efflux precede cell ejection during germination of heat-resistant ascospores of Talaromyces macrosporus - Jan Dijksterhuis; Kenneth van Driel; Mark Sanders; Douwe Molenaar; Jos Houbraken; Rob Samson; Edwin Kets (Archives of Microbiology, 2002)